Causes or Cures? Sexual Violence against Lesbian, Bisexual and Transgender Female-to-Male in Indonesia - Yolandasari, Ayu Regina (Yayasan Jurnal Perempuan, 2015)
Sexual violence is a crime in which the victims are usually blamed for being the cause. When it happened to a cisgender heterosexual woman, many people tend to use her appearance and her behavior to justify the victim blaming. It would even be more complicated for lesbian, bisexual women, or female-to-male transgender (LBT). When sexual violence happened to them, their sexual and/or gender identity tend to be added on the reasons to justify the perpetrators’ actions. Strangely, in contrast to that, this crime is also usually thought as the cause of their being LBT. This paper is aimed to explore this paradoxical thoughts of sexual violence against LBT, its effects on LBT’s lives, and efforts made to break through the paradox itself.